Communicative Exchanges and Classroom Teaching Practices of Trainee Teachers - Villalta-Paucar, M (UNIV AUTONOMA BAJA CALIFORNIA, INST INVESTIGACION & DESARROLLO EDUCATIVO, 2020)
Professional practice in initial teacher training provides situated knowledge of teaching. This paper analyzes classes taught by student teachers; six students were observed as they performed their internship for the basic-level education pedagogy degree from three accredited universities in three regions of Chile. Two consecutive classes were filmed and analyzed using conversation analysis categories. It was found that the conversation structures described are associated with types of intervention by pedagogy students in the classroom. It was also noted that the organization of classes was similar in many respects to classes by in-service teachers with more professional experience.